2013
DOI: 10.3109/01676830.2013.842253
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis on Outcomes for Endoscopic Versus External Dacryocystorhinostomy

Abstract: DCR is a procedure with high success rates. Endoscopic procedures differ greatly by technique with EM-DCR offering comparable results to EXT-DCR, without the risk of cosmetically unacceptable scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
107
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(112 citation statements)
references
References 18 publications
1
107
0
4
Order By: Relevance
“…In another study, Davies et al (16) reported that in their series of 72 patients, only 4.2% of the patients had visible scars, no remarkable scar was formed in any patients, and none of the patients were unhappy with his/her scar. In a meta-analysis, 554 EXT-DCR procedures were evaluated and the unacceptable rate of scarring for the patient was found to be 10.8% (6). In our study, it was reported that no visible scarring remained in (37/43) 86.1% of the patients who underwent EXT-DCR and a very small scar remained in (6/43) 13.9% of the patients.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In another study, Davies et al (16) reported that in their series of 72 patients, only 4.2% of the patients had visible scars, no remarkable scar was formed in any patients, and none of the patients were unhappy with his/her scar. In a meta-analysis, 554 EXT-DCR procedures were evaluated and the unacceptable rate of scarring for the patient was found to be 10.8% (6). In our study, it was reported that no visible scarring remained in (37/43) 86.1% of the patients who underwent EXT-DCR and a very small scar remained in (6/43) 13.9% of the patients.…”
Section: Discussionmentioning
confidence: 58%
“…The correction of epiphora and the prevention of dacryocystitis episodes can be considered as the success criteria in DCR. Very different success rates have been reported in the literature for both methods (4)(5)(6)(7)(8)(9). In a study, the authors suggested that the reason for such varying success rates was that there were no standard and objective methods to measure the results.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, success rates for En-DCR reported vary from 74 to 100%, but may be complicated by nasal bleeding, nasal osteotomy scarring, granuloma, osteotomyturbinate/septal synechiae, CSF-rhinorrhea, and damage to the orbital contents. [2][3][4][5][6][7] Purpose of our study is to compare and analyze the surgical outcome of both Ex-DCR and En-DCR, in terms of their success, failure, and complications in a retrospective way, in our tertiary referral center of northern India. Patients and Methods: After obtaining approval from the Hospital medical ethics committee, retrospective data were collected, on patients who underwent DCR, for a period of two years from October 2013 to September 2015, at our medical college of north India.…”
mentioning
confidence: 99%
“…12 No adjunctive procedures such as septoplasty or polypectomy were performed on any of our patients. In our opinion, if such procedures are deemed necessary they should only be performed by an otolaryngologist, as recommended by Kim et al 14 While some studies have demonstrated that such procedures improve success rates of END-DCR by improving access to the surgical site, 15 we have not found access to be difficult with decongestion of the lateral wall of the nose, after reflection and removal of the nasal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] A meta-analysis conducted in 2014 comparing the success rates of END-DCR with EXT-DCR, where success was defined as, 'resolution of symptoms and/or anatomical patency', concluded that the overall success rate of END-DCR (excluding laser-assisted approaches) was 87%, which was the same as that of EXT-DCR. 12 The authors point out that this is less than the 'oft-quoted 90-95% from case series and is likely to reflect the bias in such lower level evidence'.…”
Section: Introductionmentioning
confidence: 87%